KARAKTERISTIK PRODUK KOPI DI CAFE LIM KOK TONG PLUIT TERHADAP LOYALITAS PELANGGAN - Kevin Hadrian; Sofiani Sofiani (Kepariwisataan: Jurnal Ilmiah, 2022)
Coffee is one of the most popular drinks in Indonesia. Coffee is currently sold not only as a product, but also as part of a lifestyle along with the development of many coffee shops or coffee shops. Along with the development of business businesses engaged in food and beverages, especially coffee, many companies are trying and competing to set up various and varied businesses. Currently, the food and beverages business is a type of business that is flourishing from simple variants with various attractive and unique views of a variety of different prices according to the level of product characteristics. This study aims to determine the characteristics of coffee products at Cafe Lim Kok Tong Pluit towards customer loyalty. The results of the research in the t test show that the variable X (product characteristics) individually or partially and significantly has a significant influence. on the variable Y (customer loyalty), so it can be concluded that H0 is rejected and H1 is accepted. The results of the research in the f test show that the significance value 0.000 <0.05, so this shows that the product characteristic variables simultaneously influence customer loyalty.Keywords: Product Characteristics; Coffee; Customer Loyalty